2023
DOI: 10.4143/crt.2022.1428
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Endosonography to Detect Mediastinal Lymph Node Metastasis in Patients with Radiological N1 Non–Small Cell Lung Cancer

Abstract: Guidelines recommend that non-small cell lung cancer (NSCLC) patients with suspected hilar lymph node (LN) metastases should undergo invasive mediastinal LN staging prior to surgical treatment via endosonography. We evaluated the diagnostic performance of endosonography for detecting occult mediastinal metastases (OMM) and determined the factors associated with OMM in NSCLC patients with radiological N1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have shown that patients with central tumors, adenocarcinomas, and solid tumors had a higher prevalence of occult MLN metastases [ 8 , 14 , 26 - 28 ]. Since the prevalence of pN2-3 is high in these conditions, the positive predictive value of eN2-3 by endosonography can be increased and will allow more patients to benefit from proper nodal staging by endosonography.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that patients with central tumors, adenocarcinomas, and solid tumors had a higher prevalence of occult MLN metastases [ 8 , 14 , 26 - 28 ]. Since the prevalence of pN2-3 is high in these conditions, the positive predictive value of eN2-3 by endosonography can be increased and will allow more patients to benefit from proper nodal staging by endosonography.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with active malignancies of other organs at the time of lung cancer diagnosis were excluded. This study includes 315 study participants from a previous study at our center that analyzed the diagnostic performance of endosonography [ 8 ]. In our previous study, we presented information on the prevalence of pN2/N3, the number of lymph nodes (LNs) sampled from N2/N3 stations per patient, and sensitivity in rN1 NSCLC patients undergoing endosonography, comparing it with reports from other institutions [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 The role of EBUS-TBNA for each specific clinical scenario of normal mediastinum on PET/CT where invasive staging is recommended (cN1, ≥T2 and central cT1N0M0) has been scarcely studied. To the best of our knowledge, only two studies 6,7 investigated the usefulness of endosonography in cN1 tumours, both with a reported sensitivity of 38%. Based on this poor sensitivity, some authors have claimed that EBUS-TBNA should not be the technique of choice for invasive mediastinal staging of patients with cN1 tumours.…”
Section: Introductionmentioning
confidence: 99%